ACTIVITY BASED COSTING DESIGN ON SHREDDED ONCOM PRODUCTS BUMDES DAWUAN KALER - Mutqi Sopiawadi; Yayan Taryana; Raphael Rukito; Maya Aditya; Raisha Rahma Khairunissa; Raisha Rahma Khairunissa; Vania Aurelian; Vania Aurelian; Mita Aulia Amanda; Gandhes Dwi Puspaningtyas; Syauqy Maulana Harbi; Wahyu Imam Ibrohim (Gapura (Garba Pembangunan Masyarakat), 2025)
As technology and information advance, companies must adapt to stay competitive globally. Small and medium enterprises (SMEs) in Indonesia and other countries are key drivers of the economy. SMEs can enhance accuracy in cost determination by replacing traditional cost accounting methods with the Activity-Based Costing (ABC) system. ABC calculates costs for each activity, focusing on production process costs. This research examines the application of ABC in the shredded oncom business unit of Bumdes Kaler Subang. The study aims to determine the effectiveness of ABC in this context, using a descriptive qualitative approach with data collected through direct interviews. The results show that the ABC method accurately allocates overhead costs, resulting in a total production cost per unit of Rp. 14,572.